a3 b3 formula

By Mandeep Kumar|Updated : July 18th, 2022

The formula of a3 b3 can be seen in this post. Check the formula of (a + b)3, (a3 + b3), (a – b)3, and (a3 – b3) with example below.

Answer: The formula of (a + b)3 is a3 + b3 + 3ab (a + b).

The formula of (a3 + b3) is (a + b) (a2 – ab + b2).

The formula of (a – b)3 is a3 – b3 – 3ab (a-b).

The formula of (a3 – b3) is (a – b) (a2 + ab + b2).

The above equations can be proved true by assuming a value for ‘a’ as well as ‘b’. Let us take ‘a’ = 1 and ‘b’ = 2.

To prove (a + b)3 is a3 + b3 + 3ab (a + b), put a =1 and b = 2 in this equation.

First we will solve LHS = (a + b)3

= (1+2)3

= (3)3

= 27.

Now, take the RHS = a3 + b3 + 3ab (a + b)

= (1)3 + (2)3 + 3 x 1 x 2 (1+2)

= 1 + 8 + 6 (3)

= 1+ 8 + 18

= 27.

Here LHS = RHS, hence the equation is correct.

By following the same steps, other equations can also be verified.

Summary:

a3 b3 formula

The formula of (a + b)3, (a3 + b3), (a – b)3, and (a3 – b3) with example have been presented in this post. Check the details above.

Comments

write a comment

PO, Clerk, SO, Insurance

BankingIBPS POIBPS ClerkSBI POIBPS SOSBI ClerkRBIIDBI SORRBLICESICNainital BankOtherQuick LinkMock Test

Follow us for latest updates